VISUAL ELEMENTS AS A CONSTRUCTION MEDIA OF KOREAN CULTURE IMPERIALISM - Aditya Dwi Putra Bhakti; Moch. Fuad Nasvian (Jurnal Partisipatoris, 2022)
This study aims to find out how visual elements are used as a construction medium for cultural imperialism, especially Korean Culture, through film series production. This study uses a qualitative approach. This study uses the visual element concept of Timothy Samara with Roland Barthes' semiotic analysis method. The object under study is the Korean serial film, Squid Game Season 1 which consists of 9 episodes. The results of this study of the Squid Game series in a structured way maximize the use of elements of form and space, color, symbolic space, typography, and layout as a medium for constructing Korean cultural imperialism. The findings from this study also contribute to the science of visual communication, especially in the use of visual elements in film works.